Pemanfaatan Aplikasi Wordwall pada Pembelajaran di Program Studi PGSD Universitas Bhinneka PGRI - Nugrananda Janattaka; Aditya Pringga Satria; Ammy Aulia Renata Anny (Yayasan Al-Afif, 2025)
Learning in the Society 5.0 era is different from previous eras. The use of technology in learning provides a variety of alternatives. The interactive learning innovation in this study is the use of Wordwall as a game-based interactive learning medium that emphasises active participation learning styles for all students. The Wordwall platform used is an online quiz, where students immediately reflect their answers online and Wordwall records all student activities, which can be used as assessment material. This study aims to determine how suitable the Wordwall application is for use in the learning process by understanding student responses to this application. This study uses a qualitative method by using Wordwall in the learning process for 22 students of the PGSD study programme at Bhinneka University. Meanwhile, there are five lecturers who implement Wordwall, namely AP, NO, RF, NJ, and LS. The results of the study indicate that lecturers are able to implement evaluation using Wordwall, and lecturers are able to apply Wordwall to integrate with other applications in learning, while students' responses are more motivated in learning, students understand the material better and are able to work well together when learning in groups.